The effective model for sustainable community development / Mohammad Shatar Sabran - Sabran, Mohammad Shatar (2004)
In Malaysia there are several efforts and programs that has been implemented to develop rural communities both socially and economically. Millions of dollars and effort have been spent for that purpose. One of the popular approaches that has been used by bot h the government and the private agencies to achieve the goal is through community development projects. Community development stressed on the involvement of all parties in the projects. This would include the government, community developers, and the people in the communities. Community development is the purposeful effort by community people to learn and work together to guide the future development of their communities, making full use of their resources as well as the external resources Community development is also a process through which people and communities learn how they can help themselves. Despite having a tremendous effort and financial support from the government and the agencies involved in the programs, many of the community development projects that have been implemented were not sustainable. Most of the community development projects remained "dead" or disappeared few years after the implementation date. The projects worked great just for the first few years of the implementation. What went wrong? Why the community development projects introduced did not last longer or sustain? Perhaps the model that is going to be discussed in this article would be able to help explaining what and why most of the community development projects that have been implemented failed or did not sustain. Furthermore this model is going to illustrate step by step process of how to sustain community development projects. It is hope that the model will be used as a guideline for the government and all other interested agencies to help develop communities in this country. If this occurs, the government of Malaysia and the agencies involved will no longer waste money and efforts on community development projects that do not produce adequate returns on the investment. This will benefit the people in the communities, as the government and the agencies involved will have more money to spend on other needs such as education, infrastructures and other social development